2017
DOI: 10.1111/apt.14257
|View full text |Cite
|
Sign up to set email alerts
|

Safety of herpes zoster vaccination among inflammatory bowel disease patients being treated with anti‐TNF medications

Abstract: Our data suggest that co-administering the herpes zoster vaccine to patients who are taking anti-TNF medications is relatively safe. This study significantly expands the evidence supporting the use of herpes zoster vaccine in this population, having included an elderly group of patients with a high Charlson Comorbidity Index who are likely at a much higher risk of developing HZ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…These recommendations are in line with the recommendations by the Infectious Disease Society of America [47]. Besides, a recent study by Khan et al [68] suggests that even among patients on anti-TNF medication vaccination with the live vaccine may be safe. However, only around 21% of patients eligible for vaccination were vaccinated, as a recent study by Khan et al [69] showed.…”
Section: Human Papillomavirussupporting
confidence: 72%
“…These recommendations are in line with the recommendations by the Infectious Disease Society of America [47]. Besides, a recent study by Khan et al [68] suggests that even among patients on anti-TNF medication vaccination with the live vaccine may be safe. However, only around 21% of patients eligible for vaccination were vaccinated, as a recent study by Khan et al [69] showed.…”
Section: Human Papillomavirussupporting
confidence: 72%
“…Therefore, the vaccine needs to be given ≥3 weeks prior to the initiation of any immunosuppressant medication [44]. However, Khan et al showed that, in 59 patients treated with anti-TNF medication, of whom 12 (20%) were also using thiopurine, once they received the vaccine no case of HZ infection was seen within 0-42 days after its administration [45].…”
Section: Vaccination Rate In Ibd Patientsmentioning
confidence: 99%
“…The prevalence of tuberculosis in Japan was 17 per 100,000 population as of 2015, which was lower than that in other Asian countries, such as 322 in the Philippines, 217 in India, 80 in South Korea, and 67 in China, yet was still higher than the low-prevalence standard of 10, as is the case in many developed countries [34]. Therefore, in many Asian countries including Japan, Bacille CalmetteGuérin (BCG) is generally administered during infancy.…”
Section: Bacille Calmette-guérinmentioning
confidence: 68%